Analysis of four-year management of the waiting list for liver transplantation in Rostov region: prospects for reducing mortality of candidates listed for liver transplantation - V. L. Korobka; E. S. Pak; A. M. Shapovalov; M. U. Kostrykin; A. V. Tkachev (Медицинский вестник Юга России, 2019)
Purpose: analysis of various clinical results in patients registered in the liver transplantation waiting list (LTWL).Materials and methods: the study was carried at the Center of Surgery and Donor Coordination of the Rostov Regional Clinical Hospital using clinical, laboratory and instrumental data of 198 patients from the LTWL. 99 men and 99 women were enrolled into this study. The men age ranged from 21 to 70 years (47.8 ± 10.4 years), women age - from 18 to 66 years (49.2 ± 10.9 years). At the time of analysis of the LTWL, the average follow-up period was 14.8 ± 11.2 months. All patients were examined according to the list required for inclusion in the LTWL.Results: depending on the outcome, 198 patients from TLWL were grouped into 4 groups. The first group (delisting group) — 19 patients (9.6 %) with clinical and laboratory indicators that allowed them to be excluded from WL. The second group — 67 patients (33.8 %) who had positive clinical dynamics following therapy. The third group — 39 patients (19.7 %) who underwent liver transplantation. The fourth group — 73 patients (36.9 %) who had negative dynamics following therapy, including patients with a fatal outcome. While keeping LTWL for 4 years, 61 (30.81 %) of 198 listed patients died. The majority (40 patients) died of bleeding from varicose veins and OPPN, 17 patients died of hepatic coma and SPB. Each group represents the distribution of patients according to the MELD-Na scale, the severity of portal hypertension and hepatic encephalopathy.Conclusion: the following factors are indispensable for successful work of the transplant center: systematic work with the territories in order to expand the donor base; defining the patient priority criteria in the LTWL in order to reduce the death rate in the list; detailed examination of the patient before entering the list; forming the observation base; systematic patient observation during the pre- and postoperative period, at the rehabilitation stage, as well as at long-term periods in order to develop an effective algorithm of management of the recipient of a solid organ.